Lemongrass fibre as lost circulation material in drilling fluid / Nurul Aimi Ghazali … [et al.] - Ghazali, Nurul Aimi; Azizi, Azlinda; Alias, Nur Hashimah; Tengku Mohd, Tengku Amran; Wan Bakar, Wan Zairani (Research Innovation Business Unit, 2014)
In oil and gas industry, mud is used to help drilling operation to reach the desirable target in reservoir with different types of formations and challenges to extract the oil or gas to the surface. The functions of drilling mud are (1) to suspend cuttings to prevent it sagging at the drill bit during shutdown, (2) to transport it to the surface, (3) to cool and lubricate the drill bit, (4) to provide enough hydrostatics pressure to prevent fluids from formation enter to the wellbore and (5) to form a thin filter cake to seal the damage formation. Lost circulation is one of the most troublesome problems encountered in drilling due to uncontrolled flow of drilling fluid into the formation that is likely to happen due to ineffective filter cake. The smaller particles of drilling fluid are able to break through into the larger void spaces in the formation which lead to lost circulation. The industry uses millions of dollars a year to solve lost circulation. The negative effects of lost circulation are blow-outs, stuck pipe, lost rig time and the leasing of wells. Lost circulation materials (LCM) are drilling fluid additives that are designed to make sure that the drilling fluid circulated down the hole and return to surface for recirculation rather than loss to the formation drilled. There is a wide range of LCM that is currently being applied, depending on the viability of materials and loss rates, ranging from particles, flakes and cement gunk to chemical sealants. LCM selection is usually based on cost, nature of losses, types of drilling fluid being used and sometimes on the type of formations being drilled Thus, fibrous materials are recognized to be used as lost circulation material (LCM) in drilling fluid to prevent loss of circulation. Nowadays, most of operator interested in the ultra-deep water due to the limitation of reserves and deals with high temperature and high-pressure conditions. Oil based mud (OBM) is more preferable in high temperature conditions compared to water-based mud hence a laboratory study was carried out to investigate the effect of temperature on the performance of lemongrass with different sizes of LCM in oil-based mud. Evaluation on the filter cake and filtrate were also determined by using filter press. It was found that different temperatures and sizes have great effects on the lemongrass LCM in the oil-based mud. The optimum temperature for lemongrass LCM is 275ÂºF and with the sizes of 250 microns. Based on the result, it shows that lemongrass is able to perform a good LCM in OBM based on filtrate volume and filter cake thickness. The thickness of the filter cake obtained was in the range of 2 to 25 mm which satisfies the requirement from industry. The findings also discovered that the lemongrass with the size of 150 microns is the suitable material to be used as LCM to replace conventional LCM.